Greenfield Foreign Direct Investment and Mergers and Acquisitions : Feedback and Macroeconomic Effects - Calderón, César; Loayza, Norman; Servén, Luis (World Bank, Washington, DC, 2013)
Foreign direct investment (FDI) flows to developing countries surged in the 1990s to become their leading source of external financing. This rise in FDI volume was accompanied by a marked change in its composition: investment taking the form of acquisition of existing assets (mergers and acquisitions) grew much more rapidly than investment in new assets ("greenfield" FDI), particularly in countries undertaking extensive privatization of public enterprises. This raises two issues. First, is the mergers and acquisitions boom a one-time effect of privatization, or is it likely to be followed by a rise in greenfield investment? Second, do these two types of FDI have different macroeconomic causes and consequences in relation to aggregate investment and growth? The authors focus on establishing the stylized facts in terms of time precedence between both types of FDI, investment, and growth, using annual data for the period 1987-2001 and a large sample of industrial and developing countries. The authors find that in all samples, higher mergers and acquisitions is typically followed by higher greenfield investment, while the reverse is true only for developing countries. In industrial and developing countries alike, both types of FDI lead domestic investment, but not the reverse. Finally, neither type of FDI appears to precede economic growth in developing or industrial countries, but FDI does respond positively to increases in the growth rate.